Public Administration and Ethics in Digital Era - Kemi Anthony Emina (PINISI Discretion Review, 2020)
The ability to use and develop certain periods of societal skills of using and developing information and communication technologies greatly influences the fate and uses of these technologies in the economic, political, social and cultural spheres of society in the developmental and democratic indices of the world. Today, institutions need important information and data to maintain an efficient and productive life. Likewise, digitalization of information and data reveals new management understandings. Organizations are changing organizational structures and using hierarchical structures more flexibly and more efficiently. However, the benefits of progressively non-confidentiality of data and information are increasing in different fields, of which many social and cultural cataclysms can also follow. In particular, inequality in society is caused by the mutilation of privacy and trust In the Digital era, virtual action loses value and raises ethical issues. The inability to develop appropriate ethical principles for the virtual society deepens the effect of these problems on society. In this study, ethical perspectives of public administration in the Digital age are positively or negatively related to the situation.